The Gender Division of Work across Countries - Charles Gottlieb; Cheryl Doss; Douglas Gollin; Markus Poschke (Institute of Labor Economics (IZA), 2024)
Across countries, women and men allocate time differently between market work, domestic services, and care work. In this paper, we document the gender division of work, drawing on a new harmonized data set that provides us with high-quality time use data for 50 countries spanning the global income distribution. A striking feature of the data is the wide dispersion across countries at similar income levels. We use these data to motivate a macroeconomic model of household time use in which country-level allocations are shaped by wages and a set of "wedges" that resemble productivity, preferences, and disutilities. Taking the model to country-level observations, we find that a wedge related to the disutility of market work for women plays a crucial role in generating the observed dispersion of outcomes, particularly for middle-income countries. Variation in the division of non-market work is principally shaped by a wedge indicating greater disutility for men, which is especially large in some low- and middle-income countries.
Keywords: E24; J16; J22; O11; 330; labor supply; home production; care work; time use; gender inequality; gender norms